Utilization of Human Induced Pluripotent Stem Cells-Derived In vitro Models for the Future Study of Sex Differences in Alzheimer’s Disease - Supakul, Sopak; Okano, Hideyuki; Maeda, Sumihiro (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is an aging-dependent neurodegenerative disease that impairs cognitive function. Although the main pathologies of AD are the aggregation of amyloid-beta (Aβ) and phosphorylated Tau protein, the mechanisms that lead to these pathologies and their effects are believed to be heterogeneous among patients. Many epidemiological studies have suggested that sex is involved in disease prevalence and progression. The reduction of sex hormones contributes to the pathogenesis of AD, especially in females, suggesting that the supplementation of sex hormones could be a therapeutic intervention for AD. However, interventional studies have revealed that hormone therapy is beneficial under limited conditions in certain populations with specific administration methods. Thus, this suggests the importance of identifying crucial factors that determine hormonal effects in patients with AD. Based on these factors, it is necessary to decide which patients will receive the intervention before starting it. However, the long observational period and many uncontrollable environmental factors in clinical trials made it difficult to identify such factors, except for the APOE ε4 allele. Induced pluripotent stem cells (iPSCs) derived from patients can differentiate into neurons and recapitulate some aspects of AD pathogenesis. This in vitro model allows us to control non-cell autonomous factors, including the amount of Aβ aggregates and sex hormones. Hence, iPSCs provide opportunities to investigate sex-dependent pathogenesis and predict a suitable population for clinical trials of hormone treatment.